Lessons from a large nationwide cohort of 350 children with ovarian mature teratoma: A study in favor of ovarian‐sparing surgery. Issue 3 (29th November 2021) - Delehaye, Fanny; Sarnacki, Sabine; Orbach, Daniel; Cheikhelard, Alaa; Rouger, Jérémie; Parienti, Jean‐Jacques; Faure‐Conter, Cécile; Hameury, Frédéric; Dijoud, Frédérique; Aubry, Estelle; Wacrenier, Agnès; Habonimana, Edouard; et al.
Abstract: Background: Ovarian mature teratoma (OMT) is a common ovarian tumor found in the pediatric population. In 10%–20% of cases, OMT occurs as multiple synchronous or metachronous lesions on ipsi‐ or contralateral ovaries. Ovarian‐sparing surgery (OSS) is recommended to preserve fertility, but total oophorectomy (TO) is still performed. Design: This study reviews the clinical data of patients with OMT, and analyzes risk factors for second events. A national retrospective review of girls under 18 years of age with OMTs was performed. Data on clinical features, imaging, laboratory studies, surgical reports, second events and their management were retrieved. Results: Overall, 350 children were included. Eighteen patients (5%) presented with a synchronous bilateral form at diagnosis. Surgery was performed by laparotomy (85%) and laparoscopy (15%). OSS and TO were performed in 59% and 41% of cases, respectively. Perioperative tumor rupture occurred in 23 cases, independently of the surgical approach. Twenty‐nine second events occurred (8.3%) in a median time of 30.5 months from diagnosis (ipsilateral: eight cases including one malignant tumor; contralateral: 18 cases; both ovaries: three cases). A large palpable mass, bilateral forms, at diagnosis and perioperative rupture had a statistical impact on the risk of second event, whereas the type of surgery or approach did not. Conclusion: This study is a plea in favor of OSS as the first‐choice treatment of OMT when possible. Close follow‐up during the first 5 years is mandatory considering the risk of 8.3% of second events, especially in cases with risk factors.